BAGAIMANA PENGARUH METRIK ESG DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Lisnawati, Lisna; Koswara, Amirani Fairuz Afif Fillian (Jurnal Riset Akuntansi, 2024)
This study was conducted to examine the influence of ESG metrics and financial performance on firm value, with a sample of 68 from 17 companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sample was selected using purposive sampling techniques. ESG metrics were assessed using the SRi formula, based on 32 standard items from the Global Reporting Initiative (GRI) 300 environmental topics. Financial performance was proxied by Return on Assets, while firm value was measured by the closing price (stock closing price). The analytical method used was multiple regression analysis. The results of this study indicate that ESG metrics have a positive influence on firm value, while financial performance has a negative influence on firm value. However, ESG metrics and financial performance simultaneously have a positive influence on firm value.